Evaluation and mapping of tropical African rangelands - International Livestock Centre for Africa (International Livestock Centre for Africa, 1976)
Proceedings of the seminar on evaluation and mapping of tropical African rangelands, particular categories of rangeland survey and evaluation, review of experiences; site development, parameters and methods; sampling and data processing, cartography, with recommendations and guidelines for the future.